A wear-resistant layer, an electric power fitting containing the layer and an integrated processing method thereof
Through the multi-component electrodeposition technology of zinc-nickel-particles, an anti-wear layer is formed, which solves the problem of insufficient performance of electric power tools in terms of corrosion and wear, and achieves the efficient wear and corrosion resistance of the tools.
Patent Information
- Application Number
- CN202211213526.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2042-09-30
AI Technical Summary
The existing power tools are insufficient in terms of corrosion and wear, which leads to prone to failure when used in the power grid, and the existing anti-wear technology fails to improve the corrosion resistance and wear resistance of the tools at the same time.
Multiple composite electrodeposition technology of zinc-nickel-particles is used to form an anti-wear layer. This layer contains corrosion-resistant alloys and particles combined in the alloy. By selecting different types of particles to regulate the friction coefficient, the anti-wear and corrosion resistance of the metal tool are improved.
It realizes the efficient wear and corrosion resistance of electric power tools, reduces wear volume, and improves the overall performance of the tools, and is suitable for different application scenarios.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of surface treatment of electric power fittings, and in particular to an anti-wear layer, an electric power fitting comprising the layer, and an integrated processing method thereof. Background Art
[0002] A large number of power fittings are indispensable in the construction of power grids. Many power fittings (such as U-shaped rings, adjustment plates, connecting plates, ball head hanging rings and other connection fittings) often need to withstand large tensile forces during operation, and even need to ensure good electrical contact at the same time. Although the price of the fittings is not high, even if one is damaged, it may cause a sudden failure of the entire line, and the loss is immeasurable.
[0003] Connecting fittings have both corrosion and wear conditions. In terms of corrosion, since the transmission lines are erected in the field and exposed to various meteorological conditions all year round, the corrosion of fittings occurs all the time. The most common anti-corrosion method for fittings is hot-dip galvanizing, but the hot-dip galvanized layer will turn red rust after more than 300 hours of salt spray test. The widespread surface rust of the existing fittings directly shows that the galvanized layer is difficult to meet the on-site anti-corrosion needs of power grids, especially coastal power grid equipment. In terms of wear, breeze vibration, dancing, icing, sub-span vibration, wire de-icing and jumping all cause wear of transmission line fittings to varying degrees. The hardness of materials such as 20# steel commonly used in current connecting fittings is less than 210HV, and the wear performance is poor, which leads to the rapid failure of connecting fittings under interaction; on the contrary, if the hardness of the connecting fittings is too high, it will cause the wear components (such as wires) to break due to excessive wear, and the consequences are equally disastrous.
[0004] In addition, studies have shown that there is an interaction between corrosion and wear, and the amount of this interaction accounts for 45%-86% of the total corrosion and wear. From the perspective of the high-voltage and long-span transmission lines in operation, one of the reasons for the paralysis of the transmission lines is that the conductors vibrate or dance in the breeze under the action of icing conditions or wind loads, causing large-scale wear and corrosion of the transmission conductors and the hardware connected to them, which in turn causes local wear of the aluminum stranded wire on the outer surface of the conductor at the connection with the wire clamp.
[0005] Therefore, it is very valuable to synergistically improve the corrosion resistance and wear resistance of electrical hardware on the basis of ensuring the performance of wear-resistant components.
[0006] Among the anti-abrasion power fittings, Niu Haijun and others from the China Electric Power Research Institute used aluminizing technology to improve the wear resistance of fittings in 2019, increasing the surface hardness of fittings to 3.6 times that of hot-dip galvanizing and reducing the wear to 62.1%-31.6% of hot-dip galvanizing (depending on the loading force), but there have been no reports on the friction coefficient and corrosion resistance of this product. In 2013, Yang Yingchun and others from the China Southern Power Grid Company and Kunming University of Science and Technology used thermal spraying technology to treat the surface of fittings, and obtained a coating with a hardness 3.6 times that of hot-dip galvanizing and a wear of 58.2% of 45# steel (substrate). At the same time, the friction coefficient was reduced from 0.8 of the steel substrate to 0.65. The study also believes that the reduction in friction coefficient is a key factor in improving wear resistance. Unfortunately, there are no reports on the corrosion resistance of this product. Of course, there are also many anti-wear surface treatment technologies and products abroad. For example, Sumitomo MetalInd Ltd invented a coating that can form adhesion, lubricity, wear resistance and corrosion resistance on the surface of a metal substrate. The coating is actually formed by curing a photocurable coating prepared with photocurable resins, photopolymerization initiators, antirust pigments and antirust agents, but there has been no report on its application in hardware products; B. Veeraraghavan of the University of South Carolina in the United States prepared an amorphous Ni-Zn-P chemical plating with a high nickel content and found that its corrosion resistance is better than that of Zn-Ni, Cd and other platings, but its tribological properties are obviously limited. Summary of the invention
[0007] In order to overcome the defects of the prior art, one of the objectives of the present invention is to provide an anti-wear layer to improve the wear resistance and corrosion resistance at the same time.
[0008] One of the purposes of the present invention is to adopt the following technical solution: an anti-wear layer, comprising a corrosion-resistant alloy and particles compounded in the corrosion-resistant alloy, formed by multi-component composite electrodeposition of zinc-nickel-particles, the mass fraction of the particles in the anti-wear layer is 0-50wt%, and the thickness of the anti-wear layer is ≥8 microns;
[0009] The corrosion-resistant alloy is a zinc-nickel alloy, the nickel content is 7-20wt%, and the balance is zinc;
[0010] The particles are self-lubricating particles for reducing the friction coefficient of the anti-wear layer or friction-increasing particles or other particles for increasing the friction coefficient of the anti-wear layer; the particle size of the particles is 10 nanometers to 30 micrometers.
[0011] The present invention adopts an anti-wear layer to replace the original hot-dip galvanized layer. The alloy strengthening of zinc and nickel and the solid solution strengthening effect of forming a single γ phase can make the hardness of the corrosion-resistant alloy reach about 200HV. The thickness of the anti-wear layer of the electric power fittings is not less than 10μm, and 12μm or more is better. The thickness of the anti-wear layer on the surface of the matching bolts and nuts is not less than 8μm. The friction coefficient is regulated by the selection of particle types so that the electric power fittings can adapt to different application scenarios. When it is necessary to reduce the friction coefficient of the anti-wear layer, one or more self-lubricating particles such as hexagonal boron nitride, graphite, graphene, polytetrafluoroethylene, carbon nanotubes, and molybdenum disulfide are selected; when it is necessary to increase the friction coefficient of the anti-wear layer, one or more friction-increasing particles such as aluminum oxide, silicon carbide, zircon, garnet, barium sulfate (or barite powder), and feldspar powder are selected. The alloy composition is conducive to the formation of a stable γ phase.
[0012] Furthermore, the self-lubricating particles are at least one of hexagonal boron nitride, graphite, graphene, polytetrafluoroethylene, carbon nanotubes, molybdenum disulfide, etc.
[0013] Furthermore, the friction-increasing particles are at least one of alumina, silicon carbide, zircon, garnet, barium sulfate, feldspar powder and the like.
[0014] Furthermore, the other particles are superhard particles such as cubic boron nitride and diamond, and one or more of them can be selectively added.
[0015] Furthermore, the nickel content is preferably 9-16wt%.
[0016] The second purpose of the present invention is to solve the defects of the existing power fittings that have poor corrosion resistance and wear resistance, and to provide an anti-abrasion power fitting to improve the corrosion resistance and wear resistance of the power fittings.
[0017] The second object of the present invention adopts the following technical solution: an anti-wear electric hardware, comprising an electric hardware with a carbon steel substrate, and the above-mentioned anti-wear layer is deposited on the surface of the electric hardware.
[0018] The potential difference between the sacrificial anode corrosion-resistant alloy and the carbon steel substrate is less than the potential difference between the carbon steel substrate and zinc. The anti-wear power fittings of the present invention can withstand a neutral salt spray test for more than 1000 hours, and the wear volume is no more than 6×10 -11 m 3 (The friction pair used is Φ6mm SUS304 ball), and the friction coefficient can be as low as 0.05.
[0019] A third object of the present invention is to provide an integrated processing method for the above-mentioned anti-wear electrical hardware.
[0020] The third object of the present invention adopts the following technical solution: a method for processing anti-abrasion power fittings, the steps of which are as follows:
[0021] The electric power fitting to be processed is immersed in a solution, microparticles and a co-deposition accelerator are added to the solution, and the above-mentioned anti-wear layer is formed on the surface of the electric power fitting by multi-component composite electrodeposition;
[0022] Using intermittent stirring and co-deposition promoter to make more particles enter the anti-wear layer, the co-deposition promoter is cobalt salt and / or rare earth salt;
[0023] Add insulating balls to the plating solution, with a particle size of 1-6 mm and a dosage of 20-250 particles / L. The dosage is adjusted according to the stirring method, stirring intensity and plating tank size. The impact of the balls on the anti-wear layer on the surface of the power fittings as the cathode is used to inhibit the formation of pores in the anti-wear layer and improve the density of the anti-wear layer.
[0024] During multi-element composite electrodeposition, the cross section of the inner wall of the corner of the trough body used to hold the solution is arc-shaped.
[0025] The cross section of the inner wall of the tank corner is arc-shaped, which can effectively alleviate the precipitation of particles at the corner during composite deposition, and also make the tank liquid more evenly stirred, which is also conducive to the uniform distribution of particles in the deposition layer. The size of the tank is adjusted according to the production capacity.
[0026] The addition of insulating balls can not only stir the plating solution, reduce concentration polarization, and promote uniform dispersion of particles in the plating solution and the coating, but also inhibit the porosity of the coating through the collision of the balls with the electrode surface, thereby improving its density, and can improve the corrosion resistance and hardness of the composite coating to a certain extent.
[0027] During composite deposition, there is an interfacial force between the newly formed metal and the particles. By controlling the intermittent time of brief stirring, the scouring effect of stirring can be weakened, and the interfacial force between the newly formed metal and the particles can be fully utilized, thereby significantly increasing the content of particles in the composite deposition layer; rare earth salt ions are easily adsorbed on the surface of particles, causing the particles to absorb more positive charges, increasing the Zeta potential of the particles, and promoting the retention of the particles at the cathode, thereby increasing the amount of composite.
[0028] Furthermore, when processing anti-wear hardware with friction reducing function, self-lubricating particles or a mixture of self-lubricating particles and other superhard particles are used. When processing anti-wear hardware with friction increasing function, friction increasing particles or a mixture of friction increasing particles and other superhard particles are selected. When processing corrosion-resistant hardware that does not require tribological properties, no particles need to be added.
[0029] Furthermore, when the particle size of the self-lubricating particles is at the nanometer level, the amount thereof added to the plating solution is 0.05-5 g / L, preferably 1-5 g / L; when the particle size of the self-lubricating particles is at the micrometer level, the amount thereof added to the plating solution is 3-120 g / L, preferably 60-120 g / L.
[0030] Furthermore, when the particle size of the friction-increasing particles or other superhard particles is at the nanometer level, the amount thereof added to the plating solution is 0.05-5g / L, preferably 1-5g / L; when the particle size of the friction-increasing particles or other superhard particles is at the micrometer level, the amount thereof added to the plating solution is 2-150g / L, preferably 50-150g / L.
[0031] Furthermore, the cobalt salt is one or more of cobalt sulfate and cobalt nitrate, and the addition amount is 0.001-0.05 mol / L, preferably 0.01-0.05 mol / L; the rare earth salt is a mixture of one or more of soluble rare earth salts such as cerium sulfate, cerium nitrate, and ammonium cerium nitrate, and the addition amount is 0.001-0.025 mol / L, preferably 0.010-0.020 mol / L.
[0032] Furthermore, the tank body is a square tank body, and the cross-sections of the inner walls of its four corners are arc-shaped; or the tank body is an elliptical tank body, and an agitator is provided at each focus of the elliptical tank body; or the tank body is a circular tank body, and the circular tank body is provided with two agitators, and the two agitators are at equal distances from the inner wall of the tank body; or swirl stirring is adopted, and multiple outlets are arranged in the tangential direction of the tank body, and universal nozzles are arranged in the tank body. The plating solution forms an "inlet-tank body-outlet" cycle through a circulating pump. The inner wall of the tank body sprays the solution at a certain angle to the tank wall according to the stirring requirements of the plating solution. Combined with the circulating pump, a swirl is formed in the tank body, and the nozzle angle is adjustable. The intensity and intermittent time of the swirl are achieved by controlling the speed and start and stop of the circulating pump, and a valve is provided on the circulation pipeline.
[0033] Furthermore, the tank body is equipped with an electric heating tube. When the liquid level in the tank body is too low, the float switch drops and the electric heating tube automatically stops heating. If the float switch fails, the electric heating tube itself is equipped with an overheating protection switch. When the liquid level drops, the heating area of the electric heating tube will be exposed to the air and generate heat. When the temperature reaches the protection temperature of the overheating protection switch, the overheating protection switch will link the electric heating tube to automatically cut off the circuit and stop heating.
[0034] The beneficial effects of the present invention are as follows: the anti-wear layer of the present invention has wear resistance and corrosion resistance; the integrated processing method of the present invention realizes the synergistic effect of the corrosion-resistant alloy and the particles through the multi-component composite electrodeposition of zinc-nickel-particles, and utilizes the multiple effects of alloy solid solution strengthening, particle dispersion strengthening, fine grain strengthening and mechanical strengthening to greatly reduce the wear volume of the anti-wear layer from the comprehensive effects of hardness and friction coefficient, while giving the surface of the power fittings, matching bolts and nuts excellent corrosion resistance and wear resistance. DETAILED DESCRIPTION
[0035] The present invention is described in more detail below.
[0036] Example 1
[0037] The present embodiment provides an anti-wear layer, which includes a corrosion-resistant alloy and particles compounded in the corrosion-resistant alloy, and is formed by multi-component composite electrodeposition of zinc-nickel-particles. The mass fraction of the particles in the anti-wear layer is 0-50wt%, the thickness of the anti-wear layer is ≥8 microns, the thickness of the anti-wear layer on the surface of the power fitting is not less than 10 microns, and more preferably above 12 microns, and the thickness of the anti-wear layer on the surface of the matching bolts and nuts is not less than 8 microns; the corrosion-resistant alloy is a zinc-nickel alloy with a nickel content of 7-20wt%, preferably 9-16wt%, and the balance is zinc. This alloy composition is conducive to the formation of a stable γ phase.
[0038] The particles are self-lubricating particles for reducing the friction coefficient of the anti-wear layer or friction-increasing particles or other superhard particles for increasing the friction coefficient of the anti-wear layer; the particle size of the particles is 10 nanometers to 30 micrometers.
[0039] The self-lubricating particles are at least one of hexagonal boron nitride, graphite, graphene, polytetrafluoroethylene, carbon nanotubes, molybdenum disulfide, etc.; the friction-increasing particles are at least one of aluminum oxide, silicon carbide, zircon, garnet, barium sulfate, feldspar powder, etc.; the other superhard particles are cubic boron nitride, diamond, etc.
[0040] Example 2
[0041] This embodiment provides an anti-wear electrical hardware, including an electrical hardware with a carbon steel substrate, and the anti-wear layer described in Embodiment 1 is deposited on the surface of the electrical hardware.
[0042] Example 3
[0043] This embodiment provides an integrated processing method for anti-abrasion power fittings, and the steps are as follows:
[0044] The electrical hardware to be processed is immersed in a bath solution, microparticles and a co-deposition promoter are added to the bath solution, and the anti-wear layer described in Example 1 is formed on the surface of the electrical hardware by multi-component composite electrodeposition. When the particle size of the self-lubricating microparticles is at the nanometer level, the amount thereof added to the plating solution is 0.05-5g / L, preferably 1-5g / L; when the particle size of the self-lubricating microparticles is at the micrometer level, the amount thereof added to the plating solution is 3-120g / L, preferably 60-120g / L. When the particle size of the friction-increasing microparticles or other superhard microparticles is at the nanometer level, the amount thereof added to the plating solution is 0.05-5g / L, preferably 1-5g / L; when the particle size of the friction-increasing microparticles or other superhard microparticles is at the micrometer level, the amount thereof added to the plating solution is 2-150g / L, preferably 50-150g / L.
[0045] Intermittent stirring and co-deposition promoter are used to make more particles enter the anti-wear layer. The co-deposition promoter is selected from cobalt salt and / or rare earth salt. The cobalt salt is one or more of cobalt sulfate and cobalt nitrate, and the addition amount is 0.001-0.05 mol / L, preferably 0.01-0.05 mol / L; the rare earth salt is a mixture of one or more soluble rare earth salts such as cerium sulfate, cerium nitrate, and ammonium cerium nitrate, and the addition amount is 0.001-0.025 mol / L, preferably 0.010-0.020 mol / L.
[0046] The tank used for electroplating is used to hold the plating solution and place the stirring device and the conductor. The insulating ball is placed in the plating solution, and intermittent stirring is achieved through the stirring device. A discharge port is provided at the bottom of the tank. The stirring device includes a stirrer and a control system for controlling the operation of the stirrer; or swirl stirring is adopted, and multiple outlets are provided in the tangential direction of the tank, and universal nozzles are arranged in the tank. The plating solution forms an "inlet-tank-outlet" cycle through a circulating pump. The inner wall of the tank body sprays the solution at a certain angle to the tank wall according to the stirring requirements of the plating solution. Combined with the circulating pump, a swirl is formed in the tank body, and the nozzle angle is adjustable. The intensity and intermittent time of the swirl are achieved by controlling the speed and start and stop of the circulating pump, and a valve is provided on the circulation pipeline.
[0047] When adding insulating balls to the plating solution, the particle size of the balls is 1-6mm, and the dosage is 20-250 particles / L. It is adjusted according to the stirring method, stirring intensity and tank size. The balls are used to impact the anti-wear layer on the surface of the power fittings as the cathode to inhibit the formation of pores in the anti-wear layer and improve the density of the anti-wear layer. The material and size of the balls can be determined according to the situation. When the stirring intensity is high, balls with a slightly larger density or diameter can be selected; when the stirring intensity is low, balls with a slightly smaller density or diameter can be selected. Plastic balls are preferred. In chemical composite plating, balls with inert materials in the deposition system are preferred.
[0048] During multi-element composite electrodeposition, the cross section of the inner wall of the corner of the tank body used for placing the plating solution is arc-shaped.
[0049] The tank body is a square tank body, and the cross-sections of the inner walls of the four corners are arc-shaped; or the tank body is an elliptical tank body, and a stirrer is provided at each focus of the elliptical tank body, and can perform forward and reverse bidirectional stirring; or the tank body is a circular tank body, and the circular tank body is provided with two stirrers, and the two stirrers are at an equal distance from the inner wall of the tank body, and can perform forward and reverse bidirectional stirring. The tank body is preferably an elliptical tank body or a circular tank body.
[0050] In order to meet the process requirements, heating and cooling devices are installed in the tank. When the temperature in the tank is lower than the process temperature, heating starts. When the temperature in the tank is higher than the process temperature, cooling starts. This method ensures the accuracy of the working process temperature.
[0051] The heating device is an electric heating tube. When the liquid level in the tank is too low, the float switch drops and the electric heating tube automatically stops heating. If the float switch fails, the electric heating tube itself is equipped with an overheat protection switch. When the liquid level drops, the heating area of the electric heating tube will be exposed to the air and generate heat. When the temperature reaches the protection temperature of the overheat protection switch, the overheat protection switch will link the electric heating tube to automatically cut off the circuit and stop heating.
[0052] The control system includes a time control unit and a speed control unit. The time control unit is used to set the stirring time and intermittent time of the stirrer, which is implemented by a time relay. The intermittent time is adjusted according to the density of the plating liquid particles or the stirring intensity, and the adjustment range is 5-150s, preferably 10-80s; the speed control unit is used to control the stirring speed of the stirrer, and the stirring speed is 5-4000 rpm, preferably 600-2000 rpm, which is adjusted according to the stirring mode, stirring intensity and plating tank size; the distance between the stirrer and the bottom of the tank body is ≥10mm. The intermittent time is controlled in seconds, which not only ensures the function of stirring to transport particles to the cathode surface, but also effectively reduces the scouring effect of stirring on particles that have been retained on the cathode surface. If the density of the plating liquid particles is small, the intermittent time is adjusted down, and if the stirring intensity is large, the intermittent time is adjusted down, and vice versa. The adjustment of the stirring intensity and direction is implemented by the reducer regulator.
[0053] The present invention is based on the multiple effects of alloy solid solution strengthening, particle dispersion strengthening, fine grain strengthening and mechanical strengthening. The comprehensive effect of hardness and friction coefficient greatly reduces the wear volume of the anti-wear layer, thereby giving the power fittings excellent tribological properties:
[0054] 1. In terms of hardness, firstly, the alloy strengthening of zinc and nickel and the solid solution strengthening effect of forming γ single phase can make the hardness of the corrosion-resistant alloy reach about 200HV. Secondly, the dispersion strengthening of particles in the anti-wear layer, the fine grain strengthening caused by cathode polarization of rare earth salt additives and particles, and the mechanical strengthening caused by sphere collision can further increase the hardness of the anti-wear layer to 500HV--600HV. The hardness of hot-dip galvanizing is only about 60HV.
[0055] 2. In terms of friction coefficient, on the one hand, the friction coefficient can be regulated by selecting the type of particles so that the electrical fittings can adapt to different application scenarios. When it is necessary to reduce the friction coefficient of the anti-wear layer, one or more of self-lubricating particles such as hexagonal boron nitride, graphite, graphene, polytetrafluoroethylene, carbon nanotubes, and molybdenum disulfide are selected. When it is necessary to increase the friction coefficient of the anti-wear layer, one or more of friction-increasing particles such as aluminum oxide, silicon carbide, zircon, garnet, barium sulfate (or barite powder), and feldspar powder are selected. Second, innovative processes such as intermittent stirring and co-deposition promoters are used to promote more particles into the deposition layer. Intermittent stirring is implemented through a specific tank body, and the co-deposition promoter is one or more soluble cobalt salts or rare earth salts; stirring has the dual effect of transporting particles to the cathode and flushing particles retained on the cathode surface. The inventor's research shows that there is an interfacial force between the new metal and the particles during composite deposition. By controlling the intermittent time of simple stirring, the flushing effect of stirring can be weakened, and the interfacial force between the new metal and the particles can be fully utilized, thereby significantly increasing the content of particles in the coating; rare earth ions are easily adsorbed on the surface of particles, allowing the particles to adsorb more positive charges, increase the Zeta potential of the particles, and promote the retention of particles at the cathode, thereby increasing the composite amount. Third, a specific tank body is used to implement composite co-deposition, maintaining the stability of the solution on the basis of ensuring the intermittent stirring function. The cross-section of the inner wall of the tank corner is arc-shaped, which minimizes the precipitation of particles at the corner and improves the utilization rate of particles.
[0056] For those skilled in the art, various other corresponding changes and deformations can be made according to the technical solutions and concepts described above, and all of these changes and deformations should fall within the protection scope of the claims of the present invention.
Claims
1. An integrated processing method for anti-abrasion power fittings, characterized in that: Here are the steps: The electric hardware to be processed is placed in a solution, microparticles and a co-deposition promoter are added to the solution, and an anti-wear layer is formed on the surface of the electric hardware by multi-component composite electrodeposition; the anti-wear layer comprises a corrosion-resistant alloy and microparticles composited in the corrosion-resistant alloy, and is formed by multi-component composite electrodeposition of zinc-nickel-microparticles, the mass fraction of the microparticles in the anti-wear layer is ≤50wt%, and the thickness of the anti-wear layer is ≥8 microns; the corrosion-resistant alloy is a zinc-nickel alloy, the nickel content is 7-20wt%, and the balance is zinc; the microparticles are self-lubricating microparticles for reducing the friction coefficient of the anti-wear layer or friction-increasing microparticles or other superhard microparticles for increasing the friction coefficient of the anti-wear layer; the particle size of the microparticles is 10 nanometers to 30 microns; Using intermittent stirring and co-deposition promoter to make more particles enter the anti-wear layer, the co-deposition promoter is cobalt salt and / or rare earth salt; Add insulating balls to the solution, with a particle size of 1-6 mm and a dosage of 20-250 particles / L. Adjust the amount according to the stirring method, stirring intensity and plating tank size. Use the impact of the balls on the anti-wear layer on the surface of the power fittings as the cathode to inhibit the formation of pores in the anti-wear layer and improve the density of the anti-wear layer. During multi-element composite electrodeposition, the cross section of the inner wall of the corner of the tank used to hold the solution is arc-shaped; When mechanical stirring is adopted, the tank body is a square tank body, and the cross-sections of the inner walls of the four corners are arc-shaped; or the tank body is an elliptical tank body, and a stirrer is provided at each focus of the elliptical tank body; or the tank body is a circular tank body, and the circular tank body is provided with two stirrers, and the two stirrers are at equal distances from the inner wall of the tank body; Or adopt swirl stirring, set multiple outlets in the tangential direction of the tank body, arrange universal nozzles in the tank body, and make the plating solution form an "inlet-tank-outlet" cycle through a circulation pump. The inner wall of the tank body is sprayed with solution at a certain angle to the tank wall according to the stirring requirements of the plating solution. Combined with the circulation pump, a swirl is formed in the tank body, and the nozzle angle is adjustable. The intensity and intermittent time of the swirl are achieved by controlling the speed and start and stop of the circulation pump, and a valve is installed on the circulation pipeline.
2. The integrated processing method according to claim 1, characterized in that: The self-lubricating particles are at least one of hexagonal boron nitride, graphite, graphene, polytetrafluoroethylene, carbon nanotubes, and molybdenum disulfide.
3. The integrated processing method according to claim 1, characterized in that: The friction-increasing particles are at least one of aluminum oxide, silicon carbide, zircon, garnet, barium sulfate and feldspar powder.
4. The integrated processing method according to claim 1, characterized in that: The other superhard particles are cubic boron nitride or diamond, and one or more of them can be added selectively.
5. The integrated processing method according to claim 1, characterized in that: When the particle size of the self-lubricating particles is at the nanometer level, the amount thereof added to the plating solution is 0.05-5 g / L; when the particle size of the self-lubricating particles is at the micrometer level, the amount thereof added to the plating solution is 3-120 g / L.
6. The integrated processing method according to claim 1, characterized in that: When the particle size of the friction-increasing particles or other superhard particles is at the nanometer level, the amount thereof added to the plating solution is 0.05-5 g / L; when the particle size of the friction-increasing particles or other particles is at the micrometer level, the amount thereof added to the plating solution is 2-150 g / L.
7. The integrated processing method according to claim 1, characterized in that: The cobalt salt is one or more of cobalt sulfate and cobalt nitrate, and the addition amount is 0.001-0.05 mol / L; the rare earth salt is a mixture of one or more of cerium sulfate, cerium nitrate, ammonium cerium nitrate and other soluble rare earth salts, and the addition amount is 0.001-0.025 mol / L.
Citation Information
Patent Citations
Surface electroplating process of thin cutting tool
CN103806075A
Cyanide-free silver-based composite plating solution, silver-based composite plating layer and preparation method thereof
CN111235608A
Zn-Ni-Al2O3 nano composite deposit and its prepn. process
CN1834307A